Separation of Iridium from Hydrochloric Acid Medium Using Microspheres Containing 2-Ethylhexyl Benzimidazolyl Sulfoxide - Liu, Yan; Li, Jinfei; Huang, Zhangjie; Yang, Lin; Liu, Wanqiu (Asian Journal of Chemistry, 2015)
The extraction of iridium(IV) from hydrochloric acid medium was carried out using the microsphere containing 2-ethylhexyl benzimidazolyl sulfoxide as the extractant. The sorption was found to be fast, equilibrium was reached within 6 min. When the concentration of Ir(IV) was 200 mg L-1, nearly all of the Ir(IV) (> 99 %) was adsorbed by the microspheres in 4 mol L-1 HCl medium. The sorbed Ir(IV) ions were desorbed with 0.5 wt. % sodium hydroxide solution. The sorption data could be well interpreted by the Freundlich isotherm model with the maximum adsorption capacity of 80 mg g-1 (25 °C) of Ir(IV) on the microsphere. Iridium(IV) and rhodium(III) could be separated completely with a separation coefficient of Ir(IV) and Rh(III) (1.36 × 104) using the optimal separation parameters. The microspheres can be reused at least in 20 cycles of extraction-stripping process.